The measurement of participation in adult education. - Mary A. Collins; J. Michael Brick; Kwang Kim (Adult Education Research Conference, 1997)
This paper examines the disparate rates of participation in adult education that have been reported by the Current Population Survey and the National Household Education Survey. The authors examine issues including population coverage and sampling, survey nonresponse, the use of proxy respondents, and survey context effects.